54 cm2 Large‐Area Flexible Organic Solar Modules with Efficiency Above 13%. Issue 39 (8th August 2021) - Qin, Fei; Sun, Lulu; Chen, Hongting; Liu, Yang; Lu, Xin; Wang, Wen; Liu, Tiefeng; Dong, Xinyun; Jiang, Pei; Jiang, Youyu; Wang, Lei; Zhou, Yinhua
Abstract: Development of large‐area flexible organic solar cells (OSCs) is highly desirable for their practical applications. However, the efficiency of the large‐area flexible OSCs severely lags behind small‐area devices. Here, efficient large‐area flexible single cells with power conversion efficiency (PCE) of 13.1% and 12.6% for areas of 6 and 10 cm 2, and flexible modules with a PCE of 13.2% (54 cm 2 ) based on poly(ethylene terephthalate)/Ag grid/silver nanowires (AgNWs):zinc‐chelated polyethylenimine (PEI‐Zn) composite electrodes are reported. The solution‐processed flexible transparent electrode of AgNWs:PEI‐Zn shows low surface roughness and good optoelectronic and mechanical properties. PEI‐Zn is conductive and optically transparent. It can adhere to and wrap the AgNWs under electrostatic interaction between the negatively charged surface (AgNWs) and positively charged protonated amine groups (in PEI‐Zn). It wraps the AgNWs networks and fills the void space to achieve a smooth surface. The flexible electrode is validated in both flexible OSCs and flexible quantum‐dots light‐emitting diodes (QLEDs). Small‐area flexible OSCs show a PCE of 16.1%, and flexible QLEDs show an external quantum efficiency of 13.3%. In the end, a flexible module is demonstrated to charge a mobile phone as a flexible power source (shown in Video S1, Supporting Information). Abstract : Efficient large‐area flexible solar cells and modules are demonstrated based on a printable, transparent, low‐surface‐roughness, flexible electrode (silver nanowires:zinc‐chelated polyethylenimine). A power conversion efficiency of 13.2% is obtained for a 54 cm 2 solar module. The flexible electrode is also demonstrated in high‐performance flexible quantum‐dot light‐emitting diodes.